Socio-hydrological dynamics and water conflicts in the upper Huasco valley, Chile - Dame, Juliane; Nüsser, Marcus; Schmidt, Susanne; Zang, Carina (Frontiers in Water, 2023)
In arid regions of north-central Chile, mining activities and agricultural land use changes lead to competing water demands, water insecurity, and related conflicts. Different local and external user groups rely on the scarce water resources. This case study investigates socio-hydrological transformations in the upper Huasco valley. It builds on a mixed method approach that combines remote sensing assessments (Corona, Landsat, Sentinel-2) with a set of social science methods including interviews and an analysis of Twitter tweets. Against the backdrop of the recent mega drought, results show that the upper Huasco valley faces adverse environmental impacts and conflicts over mining activities as well as an expansion of export-oriented agriculture. While water availability largely depends on the cryosphere, remote sensing analyses show a drastic glacier decrease in the vicinity of the mining project, where three glaciers completely disappeared since 2000. Furthermore, an expansion of the cultivated area from 2,000 ha in the 1990s to about 3,210 ha occurred in the 2000s. Agricultural expansion has come to a halt and only a slight increase of 100 ha can be detected over the last decade. Interview and social media data show local concerns and discourses on issues of water scarcity and quality related to these land use changes. The study stresses the necessity of integrative assessments for a better understanding of water scarcity and water-related conflicts. Equitable water governance in climate-sensitive areas requires contextualizing land use changes and the precarious drinking water situation from a socio-hydrological perspective.